Acute splenic responses in patients with ischemic stroke and intracerebral hemorrhage. Issue 6 (June 2016) - Vahidy, Farhaan S; Parsha, Kaushik N; Rahbar, Mohammad H; Lee, MinJae; Bui, Thanh-Tung; Nguyen, Claude; Barreto, Andrew D; Bambhroliya, Arvind B; Sahota, Preeti; Yang, Bing; Aronowski, Jaroslaw; Savitz, Sean I
Animal models provide evidence of spleen mediated post-stroke activation of the peripheral immune system. Translation of these findings to stroke patients requires estimation of pre-stroke spleen volume along with quantification of its day-to-day variation. We enrolled a cohort of 158 healthy volunteers and measured their spleen volume over the course of five consecutive days. We also enrolled a concurrent cohort of 158 stroke patients, measured initial spleen volume within 24 h of stroke symptom onset followed by daily assessments. Blood samples for cytokine analysis were collected from a subset of patients. Using data from healthy volunteers, we fit longitudinal quantile regression models to construct gender and body surface area based normograms of spleen volume. We quantified day-to-day variation and defined splenic contraction. Based on our criteria, approximately 40% of stroke patients experienced substantial post-stroke reduction in splenic volume. African Americans, older patients, and patients with past history of stroke have significantly higher odds of post-stroke splenic contraction. All measured cytokine levels were elevated in patients with splenic contraction, with significant differences for interferon gamma, interleukin 6, 10, 12, and 13. Our work provides reference standards for further work, validation of pre-clinical findings, and characterization of patients with post-stroke splenic contraction.